2017
DOI: 10.1089/jpm.2016.0363
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the V66.7 Code for Palliative Care Consultation in a Single Academic Medical Center

Abstract: In a single center, the ICD-9 code V66.7 had poor sensitivity and high specificity for identifying hospitalized patients who received a palliative care consultation. Appropriate use of this code for this purpose should take these characteristics into consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
103
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(104 citation statements)
references
References 17 publications
(17 reference statements)
1
103
0
Order By: Relevance
“…In this study, 15% of patients with any frailty received billing for inpatient palliative care during their surgical hospitalization, which is higher than in other acutely ill older surgical patients . A limitation of administrative data is that coding for palliative care underrepresents the actual delivery of primary palliative care . However, given the high rates of mortality, institutional discharge, and healthcare utilization after EGS among older patients with frailty, palliative care should be routinely provided by members of the perioperative team to all of these patients as suggested by national consensus guidelines for quality palliative care endorsed by the American College of Surgeons…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 15% of patients with any frailty received billing for inpatient palliative care during their surgical hospitalization, which is higher than in other acutely ill older surgical patients . A limitation of administrative data is that coding for palliative care underrepresents the actual delivery of primary palliative care . However, given the high rates of mortality, institutional discharge, and healthcare utilization after EGS among older patients with frailty, palliative care should be routinely provided by members of the perioperative team to all of these patients as suggested by national consensus guidelines for quality palliative care endorsed by the American College of Surgeons…”
Section: Discussionmentioning
confidence: 99%
“…First, identifying palliative care in claims data is not straightforward. Studies of palliative care in patients with cancer using billing data thus far have relied on ICD‐9 codes , which lack sensitivity and encompass a wide range of services . Additionally, ICD‐9 codes are not specific for subspecialty palliative care.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that physician specialty codes, as opposed to International Classification of Diseases, 9th Revision (ICD‐9) billing codes (V66.7, ‘encounter for palliative care’), provide a more accurate estimate of palliative care use. Also, using ICD‐9 codes is suboptimal due to a poor sensitivity of 19–50% and its broad range of related services, such as hospice and ‘terminal care’ .…”
Section: Methodsmentioning
confidence: 99%
“…Recent work by Hua et al . found that, in a single centre, sensitivity and specificity of the V667 code for detecting a PC visit were 49.9% and 99.1%, respectively . This suggests that the code likely underestimates the true incidence of PC involvement.…”
Section: Discussionmentioning
confidence: 99%